2023
DOI: 10.1186/s41935-023-00333-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem interval of buried homicides in Okuku, Nigeria

Abstract: Background Post-mortem interval estimation of carcasses buried in shallow graves is a grey area in Nigerian forensic investigations. Most of the investigations and court decisions on the time of death of concealed homicides are based on assumptions in Nigeria. Therefore, this study investigated the post-mortem interval of buried remains in Okuku, Cross River State of Nigeria using porcine models. This study also provided a model account of the pattern and timeline of decomposition of buried rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other tropical decomposition studies, although not seasonal in nature, reported rates of pig carcass breakdown that are comparable to the present findings. These studies were conducted in a forest in Shenzhen City, Guangdong, China [ 58 ], forest-savanna near Okuku, Cross River State, Nigeria [ 20 , 59 , 60 ], Ekwulumini, Anambra State, Nigeria [ 61 ], and Medellín, Colombia [ 62 , 63 ]. These studies show that the decomposition data generated at the Chaminade facility can be representative of decomposition processes in other parts of the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…Other tropical decomposition studies, although not seasonal in nature, reported rates of pig carcass breakdown that are comparable to the present findings. These studies were conducted in a forest in Shenzhen City, Guangdong, China [ 58 ], forest-savanna near Okuku, Cross River State, Nigeria [ 20 , 59 , 60 ], Ekwulumini, Anambra State, Nigeria [ 61 ], and Medellín, Colombia [ 62 , 63 ]. These studies show that the decomposition data generated at the Chaminade facility can be representative of decomposition processes in other parts of the tropics.…”
Section: Discussionmentioning
confidence: 99%